Pengaruh Komposisi Media Tanam dan Plant Growth Promoting Rhizobacteria Terhadap Pertumbuhan Bibit Kakao: The Effect of Composition of Growing Media and Plant Growth Promoting Rhizobacteria on the Growth of Cocoa Seedlings - Pauliz Budi Hastuti; Ni Made Titiaryanti; Dina Mardhatilah (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2023)
To obtain quality cocoa seedlings, maintenance efforts are required during the nursery stage, including meeting the nutritional needs of the planting medium which can be in the form of organic fertilizer from goat manure and husk charcoal. In addition, efforts to improve growing media in nurseries can be used with biological fertilizers, including plant growth promoting rhizobacteria (PGPR). Goat manure for plant nutrients, as well as a source of nutrients for PGPR. The research objective was to determine the effect of media composition and PGPR on the growth of cocoa seedlings. Research with the experimental method of factorial design consisting of two factors was arranged using a completely randomized design. The first factor was soil planting medium: goat manure: husk charcoal (v/v) consisting of 3 levels: M0 = 1:0:0 (control), M1 = 1:1:0 and M2 = 1:1:1. Factor II, namely the dose of PGPR consists of 3 levels: K1 = 10 ml/seedling, K2 = 20 ml/seedling, and K3 = 30 ml/seedling. With three repetitions. Observational data were analyzed with variance at the 5% level. To find out the differences between treatments, the Duncan's Multiple Range Test was continued at 5% level. The results showed that there was no significant interaction between media composition and PGPR dosage on the growth of cocoa seedlings. The composition of the soil medium : goat manure : husk charcoal 1:0:0 and 1:1:0 gave good growth of cocoa seedlings. PGPR doses provide the same growth of cocoa seedlings.